Cement manufacturing using alternative fuels: Enhanced productivity and environmental compliance via oxygen enrichment. (15th October 2016) - Tsiliyannis, C.A.
Abstract: Use of alternative fuels (AF) in cement manufacturing is rising worldwide due to environmental benefits and associated subsidies, e.g. CO2 tradeable rights. Ιncreased kiln fluegas volumes from AFs imply lower clinker production, lower residence times in the air-pollution–control-system and removal efficiencies and elevated offgas pollutant emissions. Ever-present variations in AF composition, particularly if refuse derived, intensify operational uncertainty. A rigorous method is presented for quantifying the benefits of oxygen enrichment (OXE) in cement manufacturing, based on fundamental principles (mass and enthalpy balances). It employs a novel multidimensional formulation enabling simultaneous consideration of any number and types of AFs, isolating the invariant part of combustion stoichiometry from the OXE-dependent part and from the uncertain AF composition and flowrates. It was shown that OXE implies higher clinker production and lower fluegas and offgas volumes, while emissions are not impaired or even ameliorate, e.g. NOx emissions. Explicit formulae for clinker and offgas rates are presented, encompassing inner circuiting, direct or compound operation, fluegas bypass and heat integration of clinker cooler with secondary/tertiary air. The potency of the method and the significant benefits of OXE in cement manufacturing are demonstrated in a case study of an actual dry process clinker facility. Highlights: Alternative fuels bring along production cuts (less clinker) and higher emissions. Oxygen enriched (OXE) air is becoming available via cost effective in house devices. Acting as a nitrogen depletion mechanism OXE compensates clinker losses. OXE allows lower NOx formation rates and enhanced combustion of refractory fuels. Compliance with enacted limits results in lower actual emission rates under OXE use.